Beyond Belief: Chance, Authorship, and the Limits of Comprehension in Gerhard Richter's Strip - Romaine, James (Religions, 2019)
For nearly six decades, Gerhard Richter has challenged the conceptual and visual limits of contemporary painting. His 2011 work Strip overloads the viewer's visual perception. Richter created this unique digital print using a process that deliberately employs chance to circumvent the artist's authorship. This article examines the history of Richter's skepticism of creative authority and the strategies he has developed to realize an art that exceeds the limits of human skill and imagination. Although he remains an atheist, Richter frames his pursuit of an incomprehensible art in terms of a longing for a belief in God.